2017
DOI: 10.15403/jgld.2014.1121.264.nin
|View full text |Cite
|
Sign up to set email alerts
|

Nodule-in-Nodule Imaging Pattern in Hepatocellular Carcinoma Treated by Transarterial Chemoembolization – a Multiparametric Magnetic Resonance Imaging Study

Abstract: Background & Aims: Emerging minimally invasive treatments for hepatocellular carcinoma (HCC) can significantly improve a patient’s prognosis, but they may alter the imaging features of the treated nodules. This study focuses on a series of patients presenting with a rare pathology, the nodule-in-nodule imaging pattern of HCC, analyzes the imaging features and discusses possible approaches for the diagnosis of tumoral recurrence.Method: Nine patients recruited over two years, having HCC with nodule-in-nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Moreover, when associated, genistein can increase the apoptosis-inducing efficacy of photodynamic therapy on thyroid cancer cells, inhibiting proliferation and increasing reactive oxygen species (ROS) levels [2]. Hepatocellular carcinoma Hepatocellular carcinoma (HCC) is one of the most lethal cancers, with common recurrences after treatment, and relatively difficult to diagnose at small sizes or in particular subtypes [13,47]. HCC commonly develops on liver cirrhosis, this disorder adding further complications such as variceal bleeding, ascites, cardiomyopathy, and hepatic encephalopathy [62,70].…”
Section: Thyroid Cancermentioning
confidence: 99%
“…Moreover, when associated, genistein can increase the apoptosis-inducing efficacy of photodynamic therapy on thyroid cancer cells, inhibiting proliferation and increasing reactive oxygen species (ROS) levels [2]. Hepatocellular carcinoma Hepatocellular carcinoma (HCC) is one of the most lethal cancers, with common recurrences after treatment, and relatively difficult to diagnose at small sizes or in particular subtypes [13,47]. HCC commonly develops on liver cirrhosis, this disorder adding further complications such as variceal bleeding, ascites, cardiomyopathy, and hepatic encephalopathy [62,70].…”
Section: Thyroid Cancermentioning
confidence: 99%
“…With a mortality of 9.1% worldwide, HCC is the fifth most common cancer and is considered a significant global health burden, by itself and through its potential unnoticeable or overt complications [24]. With recent progress, diagnosis hindrances of rare or atypical forms of HCC have been surmounted, and novel therapies appear promising in complementing the available resources for managing this disease [57]. However, a better understanding of the underlying pathological mechanisms in the development of HCC may uncover more efficient ways to limit tumor growth and dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study performed by Kang et al [35] showed a low tumor recurrence rate during long term follow-up after RFA treatment of inner nodules. Conversely, Scheau et al [36] reported 9 patients with nodule-in-nodule architecture, all with progressive disease on MRI follow-up examination performed one month after TACE. In our population we had two patients with a second nodule-in-nodule architecture appearing as hyperintense on HBP 258 and 459 days after treatment (RFA or TACE, respectively).…”
Section: Discussionmentioning
confidence: 99%